2016
DOI: 10.1111/jch.12949
|View full text |Cite
|
Sign up to set email alerts
|

Liddle syndrome: clinical and genetic profiles

Abstract: Liddle syndrome is a rare autosomal dominant monogenic form of hypertension. The authors analyzed clinical and genetic features of 12 cases of Liddle syndrome, the largest sample size ever reported. Clinical data were studied retrospectively. The exon 13 of the β and γ subunits of the epithelial sodium channel were amplified and sequenced in the peripheral blood leukocytes of the patients. The onset age of the 12 patients was 15.5±3.3 years. Their blood pressures were poorly controlled, and serum potassium lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 10 publications
1
38
0
1
Order By: Relevance
“…LS patients lacking a family history have also been noted. Cui et al reported that de novo pathogenic variants accounted for 50% of cases, 26 and Yang et al found that 86% index cases with LS had a family history. 25 Consistent with our review in this study, only 4 (10%) pediatric cases were isolated with de novo pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LS patients lacking a family history have also been noted. Cui et al reported that de novo pathogenic variants accounted for 50% of cases, 26 and Yang et al found that 86% index cases with LS had a family history. 25 Consistent with our review in this study, only 4 (10%) pediatric cases were isolated with de novo pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Consistent with our review in this study, only 4 (10%) pediatric cases were isolated with de novo pathogenic variants. 13 , 26 , 27 Although a family history of childhood hypertension is a clue for pediatric LS, physicians should consider the isolated LS individual with a de novo pathogenic variant.…”
Section: Discussionmentioning
confidence: 99%
“…On average, hypertension develops around the second decade of life (15.5 ± 3.3 years) [10], with variation in the age of onset and severity of hypertension [6]. Without treatment, subjects will present with complications of severe hypertension during the third or fourth decade of life.…”
Section: Liddle Syndromementioning
confidence: 99%
“…Since increased luminal ENaC in the distal nephron is the common final mechanism for MR-mediated sodium reabsorption, Liddle syndrome resembles states of mineralocorticoid excess. The classical clinical presentation is severe hypertension in a young patient, with hypokalemia and metabolic alkalosis, in the setting of suppressed renin; however, unlike PA, aldosterone levels are low or undetectable and the syndrome does not improve with MR antagonist therapy [ 73 , 74 , 75 , 76 ]. The diagnosis of Liddle syndrome can be confirmed by genetic sequencing of the SCNN1B and SCNN1G genes, which encode for the β and γ subunits of ENaC [ 75 ], or the SCNN1A gene [ 77 ], and the treatment of choice are ENaC inhibitors such as amiloride or triamterene [ 74 ].…”
Section: Liddle Syndromementioning
confidence: 99%